The Influence of Compensation and Work Motivation on Employee Performance in The Personnel Department of The Ministry of Law and Human Rights - dolly, Dolly Terxy; Christina N. Sihombing; Poerwaningsih Soekarno (Universitas Kristen Indonesia, 2024)
In efforts to improve performance of employees of an organization, there are several ways such as providing proper compensation to employees. A leader must be able to motivate his employees in achieving success at the strategic goals of employee performance. Compensation is very important so that it can have a positive impact on employees in order to increase their motivation at work and improve their overall performance. The purposes of these studies are to finding out how compensation and motivations affect employee performance, and how it impacts the performance of the Personnel Agency of Ministry of Law and Human Right as the object of these research. In this study, the population sample consisted of 50 employees. These research use a quantitative approach that is descriptives in natured. To investigate the difference between work compensation and employee motivation, an analysis was carried out using primary data which was collected through observation, interviews, and distributing questionnaires. The analyst was perform using the Statistically Products and Services Solution (SPSS) software version 26. The data analyst technique in these studies use multipled linear regressions. The result of the studies show that compensation and motivations have a positive and significancy effects on employee performances either partial or simultaneous. Based on results of simultaneous influence hypothesis, compensations and motivations on employee performances obtained a coefficient of determination of 66.1%, and other variables that are influenced by 33.9%. So, it can be concluding that compensations and motivations affecting employee performances at the Personnel Agency of Ministry of Law and Human Right. Keywords: Compensation, Work Motivation, Employee Performance